PRODUCTIVITY AND GRAIN QUALITY OF THE NEW WINTER SOFT WHEAT VARIETY ‘IRIDAS’ - N. A. Morozov; V. V. Ivanov; I. V. Samsonov; T. V. Ryabova (Зерновое хозяйство России)
Winter wheat is the most important food crop, which has a significant share in the structure of the grain area of Russia. The production of high-quality wheat grain is limited by significant variation and sharp fluctuations of the soil-climatic and other factors both within the regions and through the years. All this negatively affects the amount of productivity and its quality. The development of new varieties with high productivity and at the same time high-quality grain and flour, regardless of growing conditions, is an urgent and present task for plant-breeding. The tasks in the selection work of the FSSP “Prikumskaya Experimental Breeding Station” to increase the adaptive traits were fulfilled due to the development of the new winter wheat varieties which combine better productivity and grain quality. In 2015–2016 the varieties ‘Kadril’, ‘Iridas’ and ‘Korona’ were given to the State Variety Testing. Due to the positive results of testing in the North Caucasus region the new variety ‘Iridas’ was included in the State List of Breeding Achievements in 2019. The variety was obtained as a result of individual selection from the hybrid population ‘Prikumskaya 140’ × ‘Kroshka’. During the years of the State Variety Testing (2017-2018) at the plots of the Stavropol Territory, the variety ‘Iridas’ showed productive advantages in the extremely dry and arid zones compared to the standard varieties ‘Grom’ and ‘Ayvin’ with an increase of 0.31–0.43 t/ha, respectively. The maximum productivity (10.79 t/ha) during the years of testing was obtained at the Stavropol SVTS. The variety’ Iridas’ produces large kernels with high baking characteristics. According to ARCVQE, quality indicators of ‘Iridas’ grain meet the standards for valuable wheat. The protein percentage in the grain is 13.0, gluten percentage is 30.4, IGD is 67.